Accounting Profession and Industrial Revolution Era 4.0: Opportunity or Threat? - Solikhatun, Ismi; Sari, Ratna Candra; Nurfatmawati, Lisa (Universitas Negeri Malang, 2023)
The industrial revolution era 4.0 has changed the manual-based to technology-based systems. The automation of financial system in business has shifted the accounting profession. This study aimed to evaluate the impact of industrial revolution 4.0 era whether as opportunity or threat faced by accountant. This study provided a perspective of industrial revolution 4.0 towards the accounting profession and the existing opportunities and threats. This systematic review research used a stage model previously developed by Chitu Okoli. This study used the related articles from various journals. The industrial revolution offers users to possibly change the data and information and companies to become more effective and efficient. Industrial revolution has impacted the number of workers due to the automation in accounting activities. On the other hand, industrial revolution provides various job opportunities in accounting profession. The development of technology still cannot replace the role of accountants, because humans are equipped with emotional intelligence unlike technology. Therefore, various types of technology used in industrial revolution era 4.0 still need the involvement of humans. Anyone with special Accounting expertise and competence will have these opportunities. This study is expected to provide contributions related to the views on opportunities and challenges for the profession of accountants in industrial revolution era 4.0. This study possibly encourages accountants to improve their skills and professionalism, especially on the accounting systems which cannot be completed by machince and still require the involvement of humans.